Pilgrimage Tour Mobility between Nepal and India - Ajay Khadka, Sateesh Kumar Ojha, Dinesh Basnet (International Journal of Advanced Science and Technology, 2020)
There is a great affiliation of pilgrimage tour in Nepal and India. This paper examines, mobility in connection to its effect on tourism industry, reflecting scope by comparing data, and its socio-cultural analysis. Religion is the main reason for high mobility as there are numerous Hindu and Buddhist association between these countries. Hence, This paper draws an understanding of religion connectivity with data presentation and linkage on various religious trails. This study basically uses trend analysis as method applying on several data obtained from government and other sources. The results are then compared to each nation’s potential mobility and socio-economic transaction. There are promising results for pilgrimage tour mobility as these nations’ shares common religious destinations and values.